Violet Darger : Bad Blood - Book 4 - Vargus, L. T.; McBain, Tim ([Place of publication not identified] : Smarmy Press, 2018)
The body slumps over the steering wheel. Pools of blood going tacky on the dash. Two shots to the back of the head. A mafia-style hit in a small town. Special Agent Violet Darger must make sense of this savagery.
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees; Fiction; Murder -- Investigation; Fiction; FBI; Michigan -- Fiction; Thrillers (Fiction).; Detective and mystery fiction